Implikasi Dan Dampak Hukum Bagi Pegawai Aparatur Sipil Negara Dalam Kasus Nikah Siri - Mia Ramadhania (Riviera Publishing, 2025)
Spotlight for the general public. Viewed from the perspective of employee status, ASN is a civil servant who should be an example for the community in implementing and complying with every applicable law and regulation. Marriage rules for civil servants have been strictly regulated in Government Regulation Number 10 of 1983 concerning Marriage and Divorce Permits for Civil Servants as amended by Government Regulation Number 45 of 1990 concerning Amendments to Government Regulation Number 10 of 1983 concerning Marriage and Divorce Permits for Civil Servants. The provisions regarding marriage, marriage permits and divorce have been clearly regulated in the regulation and even sanctions for civil servants who violate these provisions are also regulated. However, the discussion regarding unregistered marriage/unregistered marriage in the regulation has not been rigidly stated, this is what becomes a loophole for ASN to carry out unregistered marriages. In his research, the author used the doctrinal legal research method. This research uses document or literature study techniques, then conducts analysis using qualitative analysis methods.